2016
DOI: 10.1136/neurintsurg-2016-012777
|View full text |Cite
|
Sign up to set email alerts
|

Variable MR and pathologic patterns of hemorrhage after iodinated contrast infusion in MCA occlusion/reperfusion model

Abstract: IRCM and saline induced different MRI signal and pathologic patterns in our sample. We postulate that T2 hypointensity with no GRE hypointensity might be associated with IRCM deposition; and decreased frequency of PeH after iodixanol infusion and the presence of HF almost exclusively in the IRCM group might represent a direct/indirect effect of contrast infusion/deposition in the brain parenchyma after reperfusion. Our results support previous observations in IMS III and are hypothesis generating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Although dual-energy CT and MRI have been indicated to be the method of choice for reliable detection of hemorrhage in patients with hyperdensities after thrombectomy, there remain questions of the value of CT findings in the first follow-up to predict hemorrhage. 10,18,19,21,35 A recent study has demonstrated that early subtle CT findings strongly predict hemorrhagic transformation, but it has not included areas of hyperdensity as a predictor. 5 Another recent study proposed a metallic hyperdense sign on CT performed immediately after thrombectomy, defined as a focal area superior to 1.0 cm in diameter with maximum CT density superior to 90 HU identified within the non-petechial intracerebral hyperdense lesion in the basal ganglia, which could predict the occurrence of parenchymal hemorrhage at 24 h. 27 However, a smaller cohort publication has questioned the use of density thresholds that would not allow a reliable differentiation between hemorrhage and contrast staining on immediate post-interventional CT. 11 In our cohort, we use the high-density sign without an HU threshold; however, logistic regression showed that increasing CT density significantly increases the odds of hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although dual-energy CT and MRI have been indicated to be the method of choice for reliable detection of hemorrhage in patients with hyperdensities after thrombectomy, there remain questions of the value of CT findings in the first follow-up to predict hemorrhage. 10,18,19,21,35 A recent study has demonstrated that early subtle CT findings strongly predict hemorrhagic transformation, but it has not included areas of hyperdensity as a predictor. 5 Another recent study proposed a metallic hyperdense sign on CT performed immediately after thrombectomy, defined as a focal area superior to 1.0 cm in diameter with maximum CT density superior to 90 HU identified within the non-petechial intracerebral hyperdense lesion in the basal ganglia, which could predict the occurrence of parenchymal hemorrhage at 24 h. 27 However, a smaller cohort publication has questioned the use of density thresholds that would not allow a reliable differentiation between hemorrhage and contrast staining on immediate post-interventional CT. 11 In our cohort, we use the high-density sign without an HU threshold; however, logistic regression showed that increasing CT density significantly increases the odds of hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…9,12 Clinical outcomes of these hyperdensities on CT have been investigated previously; however, their relationship with hemorrhagic transformation after treatment and their prognosis value are not entirely understood. 8,12,21,22…”
Section: Introductionmentioning
confidence: 99%
“…The study found that unadjusted and adjusted results for efficacy and safety end points favored the use of iodixanol and concluded that it contributed less endothelial cytotoxic effect to the thrombotic process. In a subsequent MCA occlusion/reperfusion model in rats, Morales et al 18 confirmed their previous results and hypothesized that the presence of HT may represent a direct/indirect effect of radiographic CM in the brain parenchyma, with less impact of IOCM iodixanol compared with LOCM iopamidol. These promising prior investigations have not yet been extended to larger patient cohorts in the real-world setting.…”
mentioning
confidence: 63%
“…stronger T2-shortening effect than IODNS. These results could be explained by 2 hypotheses 9,14,15 : First, the T2-shortening effect of blood caused by the paramagnetic mechanism was much stronger than that of the bound water and dipole-dipole interaction effects of the iodinated contrast agent. Second, the bound water and dipole-dipole interaction effects of the iodinated contrast agent were weaker in the blood-mixed environment than in the watermixed environment.…”
Section: Discussionmentioning
confidence: 97%
“…These results correspond well with those of earlier studies. 9,14,15 The mechanism of the T2shortening effect of the iodinated contrast agent is not well-known, but the bound water effect and dipole-dipole interaction theories have been suggested as the most important mechanisms. 16,17 In general, the T2-shortening effect is explained by 3 major mechanisms: paramagnetism, bound water effect, and dipole-dipole interaction.…”
Section: Discussionmentioning
confidence: 99%